2014
DOI: 10.4236/ojog.2014.42012
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted instillation of epinephrine and levobupivacaine enables cornual excision and anatomical reconstruction in unruptured cornual pregnancy

Abstract: The objective of this report is to describe the possible use of intramiometrial vasoconstrictive agents for laparoscopic management of interstitial pregnancy and the consequences in anatomical results and reproductive outcomes. Cornual resection can be performed by laparoscopy, but the high vascularization of this area may result in profuse bleeding and laparoscopic suturing under these conditions might be impossible for the majority of the surgeons. We present a case that describes the possible use of intrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Similar works were conducted by Zullo et al, who used bupivacaine plus epinephrine during Laparoscopic myomectomy, and Gilabert-Estelles et al, who used epinephrine and levobupivacaine in cornual pregnancy to reduce blood loss. 14,15 Some published data from Fletcher et al, Helal et al, and Ikechebelu et al, who used Foley's catheter as a uterine tourniquet during myomectomy, however, and to our knowledge, our work was unprecedented to compare tourniquet using Foley's catheter versus intra-myometrial injection of bupivacaine plus epinephrine in reducing blood loss in abdominal myomectomy. [16][17][18] Ikechebelu et al, however, concluded that the use of tourniquet might be limited with large cervical or intra-ligamentry fibroids.…”
Section: Discussionmentioning
confidence: 87%
“…Similar works were conducted by Zullo et al, who used bupivacaine plus epinephrine during Laparoscopic myomectomy, and Gilabert-Estelles et al, who used epinephrine and levobupivacaine in cornual pregnancy to reduce blood loss. 14,15 Some published data from Fletcher et al, Helal et al, and Ikechebelu et al, who used Foley's catheter as a uterine tourniquet during myomectomy, however, and to our knowledge, our work was unprecedented to compare tourniquet using Foley's catheter versus intra-myometrial injection of bupivacaine plus epinephrine in reducing blood loss in abdominal myomectomy. [16][17][18] Ikechebelu et al, however, concluded that the use of tourniquet might be limited with large cervical or intra-ligamentry fibroids.…”
Section: Discussionmentioning
confidence: 87%
“…Review of literature revealed two studies investigating the use of bupivacaine plus epinephrine during gynaecological operations. The first was carried out by Zullo et al [12] who used bupivacaine plus epinephrine during laparoscopic myomectomy, while Gilabert-Estelles et al [20] tested the use of epinephrine and levobupivacaine in laparoscopic excision and reconstruction of intact cornual ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%